The Influence Risk Factors of Hypertension at the Community Coverage with the 35-54 years old: A mini study in the Meuraxa Health Community Center, Banda Aceh, Indonesia - Masyudi Masyudi; Evi Dewi Yani; Muhammad Ridhwan; Husna Husna; Teuku Muhammad Rafsanjan (International Conference on Multidisciplinary Research, 2022)
Through a preliminary study, data obtained that the number of hypertensive patients at the Meuraxa Health Center in Banda Aceh City for 2 (two) years in hypertensive patients in 2014 there were 542 visits and in 2015 there were 787 visits and ranked 1 (first) out of twenty one distributions. disease at the Meuraxa Health Center Banda Aceh. And at the beginning of 2016, January, February and March it was found that the number of visits increased to 249 visits. This study uses an analytical method, using a "cross sectional" method. The population in this study is all people aged 35-54 years who are also at risk of hypertension, amounting to The purpose of this study was to find out what factors were associated with the incidence of hypertension at the age of 35 - 54 years in the working area of the Meuraxa Health Center in Banda Aceh City in 2016. The results showed that there was a relationship between family history and the incidence of hypertension at the age of 35 - 54. years in the working area of the Meuraxa Health Center in 2016. (p-value = 0.010 < = 0.05), there is a relationship between smoking habits and the incidence of hypertension at the age of 35 - 54 years in the working area of the Meuraxa Health Center in 2016 (p-Value = 0.022 < = 0.05), There is a relationship between activity and the incidence of hypertension at the age of 35 - 54 years in the working area of the Meuraxa Health Center un 2016. (p- Value = 0.001 < = 0.05). For the Meuraxa Health Center to provide information to the surrounding community about the factors that can cause hypertension and provide counseling about negative impacts and how to prevent them.